KRISIS LINGKUNGAN ANTARA KEBIJAKAN PENGELOLAAN LINGKUNGAN DAN ETIKA LINGKUNGAN - Godefridus Samderubun; Edoardus Ernes Maturbongs (SOCIETAS, 2014)
There is no denying that a variety of environmental cases that occur now both at national and at global scope based largely on human perlaku, this paper highlights the environmental crisis that occurred in Indonesia and one of the fundamental problems in the management of the environment and natural resources rights -hak environmental and environmental justice.This paper is the result of the study or review of the literature on the phenomenon of environmental damage both locally and globally, based on the facts on the ground. Finally, we need to realize that the idea to create the environment and the welfare of local communities need to be transformed into a strategy and movement, 1) the issue of water; 2) land; 3) air; 4) mineral / mining; 5) forest; 6) marine and coastal; 7) settlement; 8) cultural landscape; and 9) animals and other creatures. These groupings will be useful to fight for the principles of right and justice in the real movements, as far as not looking at each sector of the segmentary / partial that is first is to make structural changes in regulatory framework and political practices of natural resource management. Both are pengkuatan local institutions and farmers.